Formação leitora de professores : o que nos dizem as propostas de formação continuada colimadas nos projetos políticos de desenvolvimento dos CEFAPROS? - Costa, Alessandra (2022)
This research is associated with the Graduate Program in Education at the University Campus of Rondonópolis and the Federal University of Mato Grosso (PPGEdu-CUR-UFMT), in the research line of Language Culture and Knowledge Construction: historical and contemporary perspectives, and with the Literacy and School Literacy Research Group (ALFALE). The object of this study is reading and the proposals of continuing training of CEFAPRO teachers regarding teacher reading training. The research intends to discuss and answer the following question: What are the existing contributions and weaknesses in the continuing education proposals offered by Cefapros for the development and promotion of reading for literacy teachers and Portuguese teachers in Elementary Schools in the state education network, regarding their reading training? As secondary questions, it is proposed: Does the diagnosis that constitutes the Political Project for the Development of Cefapros (PPDC), in theory, built from the needs of schools, points to the need for continuing education that includes the development of reading? What are the approaches and the place that reading occupies in the continuing education proposals offered by Cefapros to teachers? By seeking answers to these questions, it was established as a general objective to analyze the contributions and possible weaknesses in proposals for continuing education offered by Cefapros for the development and practice of reading for literacy teachers and Portuguese teachers of Elementary Schools of the state education network. The specific objectives are: To verify if the Political Project of the Cefapros refers to the need for continuing education that includes the reading of literacy teachers and Portuguese teachers; To identify if there is a need for continuing education that includes the improvement of teachers' reading in the diagnosis of the Political Project of Cefapros, constituted by demands that emerge from the schools in the network; To relate the needs presented in the diagnosis with the continuing education proposals offered annually by the training centers; To analyze the place and meaning of reading and reading training of teachers in proposals for continuing education. The research used a qualitative approach, and the methodological procedures were documentary research, through content analysis, based on Bogdan and Biklen (2006), Bardin (2016), and Franco (2018). Furthermore, the main authors who supported the study were: Gandin (2001) and Veiga and Fonseca (2008), who based the discussions on the Political Project, and Vasconcellos (2002), those related to the diagnosis. Nóvoa (2014), Imbernón (2011), among others, based the reflections on teacher training and Rocha (2001, 2010, 2019), those concerning Cefapro. The theoretical contribution regarding the reading training of teachers was based on Silva (2014), Kleiman (2011-2013), Yunes (2016), Andrade (2007). The data showed that, although proposals for continuing education that address the theme of reading and teacher reading training permeate the documents, most of them are related to overcoming the low performance of students in external and internal evaluations, leaving 3% of the proposals to contemplate the objective of this research. The result of the investigation pointed to the need to reflect on the process of continuing education of Cefapros, to overcome fragmentation, articulating actions with the real needs of teachers, considering the diagnosis beyond the indexes, aiming to pave the way for the promotion of significant changes in reading teaching activities and practices in a perspective of training critical individuals.